2004
DOI: 10.1007/bf03018772
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma and pregnancy: a case report and review of anesthetic management

Abstract: The primary goals in the management of pheochromocytoma in pregnancy are early diagnosis, avoidance of a hypertensive crisis during delivery and definitive surgical treatment. Timing of surgical resection will depend on the gestational age at which diagnosis is made. Cesarean section is the preferred mode of delivery when the tumour is still present. This case illustrates that with antenatal diagnosis, advanced methods of tumour localization, adequate preoperative adrenergic blockade and team planning, pheochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 17 publications
0
51
0
1
Order By: Relevance
“…These include increases in intraabdominal pressure, fetal movement, uterine contraction, process of delivery, an abdominal surgical intervention, and even general anesthesia. 2,4,5 In our small series, only 1 patient presented with "typical" presentation features of the disorder, which is paroxysmal hypertension, associated with headaches, sweating, and tachycardia. Two patients were diagnosed initially with gestational diabetes, which, in these cases, may have been explained by the effect of the excess catecholamines on glucose metabolism by inhibition of insulin secretion or by induction or aggravation of insulin resistance.…”
Section: Discussionmentioning
confidence: 70%
“…These include increases in intraabdominal pressure, fetal movement, uterine contraction, process of delivery, an abdominal surgical intervention, and even general anesthesia. 2,4,5 In our small series, only 1 patient presented with "typical" presentation features of the disorder, which is paroxysmal hypertension, associated with headaches, sweating, and tachycardia. Two patients were diagnosed initially with gestational diabetes, which, in these cases, may have been explained by the effect of the excess catecholamines on glucose metabolism by inhibition of insulin secretion or by induction or aggravation of insulin resistance.…”
Section: Discussionmentioning
confidence: 70%
“…Cesarean section and simultaneous removal of the tumor is the recommended approach [135]. Anesthetic management for this situation is discussed in detail in the article by Dugas and colleagues [136].…”
Section: Pheochromocytoma In Pregnancymentioning
confidence: 99%
“…This correlation is explained by the findings of Venkatesha et al who demonstrated that soluble endoglin acts by antagonizing an angiogenic molecule known as transforming growth factor beta-1, which is important in mediating nitric oxide-dependent vasodilatation and in keeping the lining of blood vessels healthy 25 Therefore, excess secretion of soluble endoglin leads to severe vasoconstriction, with resulting hypertension, and leakage of proteins into the tissues and urine. 26,27 Experimental evidence further supports the contribution of soluble endoglin to the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 97%